Pengaruh Remunerasi terhadap Kualitas Pelayanan dan Turnover Intention Dokter Spesialis di RSUD Sultan Imanuddin Pangkalan Bun - Lazuardy, Muhammad Azhary; Hidayat, Dasrun; Bagenda, Wahyuddin (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
Hospitals depend on their human resources (HR) performance for effective operations. Efficient HR management helps recruit, develop, and retain skilled personnel. Competitive remuneration plays a key role in attracting and retaining high-quality HR by enhancing motivation, satisfaction, and loyalty, which influence service quality and turnover intentions. This study examined how remuneration affects service quality and turnover intentions among specialist physicians at RSUD Sultan Imanuddin Pangkalan Bun, Indonesia. This study used a cross-sectional design and a survey data collection technique, the total sampling, 39 out of 42 specialist physicians participated. Statistical analysis using the SEM-PLS. The result revealed salary and benefits (remuneration) had no significant impact on service quality (path coefficient -0.008, p>0.05). However, remuneration significantly influenced physicians' turnover intentions (path coefficient -0.675, p<0.05), with lower remuneration increasing the likelihood of physicians leaving. Nevertheless, turnover intentions did not have a significant effect on service quality (path coefficient 0.119, p>0.05), and low remuneration did not directly impact service quality (path coefficient -0.081, p>0.05). The study finds that remuneration affects turnover intention but not service quality. The hospital should explore other factors affecting service quality and develop a fair, transparent, competitive remuneration policy to retain high-quality specialist physicians.